"I know it's just pouring it from the tap, but it's not easy": Motivational processes that underlie water drinking. (1st September 2021) - Rodger, Amy; Wehbe, Lara H.; Papies, Esther K.
Abstract: Water drinking behaviour is under-researched despite the prevalence and adverse health consequences of underhydration. We conducted a qualitative exploration into the motivational processes underlying water drinking, informed by a grounded cognition perspective on desire and motivated behaviour. We interviewed and analysed data from 60 participants stratified by age, gender, and education level using thematic analysis, to generate three key themes. "Water as situated habits, " suggests that participants form and maintain situated water drinking habits, so that within certain situations they regularly drink water. However, participants who situated their water intake only in one key situation (e.g., work routine), had low and inconsistent intake when they left this situation. Some situations happened so infrequently during the day (e.g., before bed) that participants' daily water intake was low. Many participants reported drinking water in reaction to thirst cues, but these were easily suppressed or ignored, so that water drinking was inconsistent. Participants who saw drinking water as part of their self-identity had consistent and high water intake across a variety of situations. "Knowledge and attitudes, " suggests that few participants had knowledge or attitudes that promoted water intake (e.g., perceived water as positive or understood the importance of hydration). "Strategies underlying attempts to increase intake" suggests that many participants lacked insight into strategies to increase water intake, although they spontaneously discussed attempts to drink more. This lead to ineffective attempts at behaviour change. Participants' mentions of dehydration and their responses to a urine colour chart suggested that many participants were possibly underhydrated. Our findings suggest that interventions and practitioners attempting to increase water intake need to increase knowledge about the importance of hydration, and encourage individuals to develop effective situated water drinking habits.